Effects of Interleukin-4 (IL-4)-releasing microparticles and adoptive transfer of macrophages on immunomodulation and angiogenesis. (May 2023) - Risser, Gregory E.; Machour, Majd; Hernaez-Estrada, Beatriz; Li, Dong; Levenberg, Shulamit; Spiller, Kara L.
Abstract: Macrophages are major regulators of angiogenesis in response to injury, but the mechanisms behind their diverse and phenotypically specific functions are still poorly understood. In particular, the effects of interleukin-4 (IL-4) on macrophage behavior have been well studied in vitro, but it remains unclear whether the release of IL-4 from biomaterials can be used to control macrophage phenotype and subsequent effects on angiogenesis in vivo. We used the murine hindlimb ischemia model to investigate the effects of IL-4-releasing poly(lactic- co -glycolic acid) microparticles co-delivered with IL-4-polarized macrophages on host macrophage phenotype and angiogenesis in vivo. We established a minimum dose of IL-4 required to modulate macrophage phenotype in vivo and evaluated effects on macrophage subpopulation diversity using multidimensional flow cytometry and pseudotime analysis. The delivery of IL-4-releasing microparticles did not affect the density or size of blood vessels as measured by immunohistochemical (IHC) analysis, but it did increase perfused tissue volume as measured by 3D microcomputed tomography (microCT). In contrast, the co-delivery of IL-4-releasing microparticles and exogenously IL-4-polarized macrophages increased the size of blood vessels as measured by IHC, but without effects on perfused tissue volume via microCT. These effects occurred in spite of low recovery of adoptively transferred macrophages at 4 days after administration. Spatial analysis of macrophage-blood vessel interactions via IHC showed that macrophages closely interacted with blood vessels, which was slightly influenced by treatment, and that blood vessel size was positively correlated with number of macrophages in close proximity. Altogether, these findings indicate that delivery of IL-4-releasing microparticles and exogenously IL-4-polarized macrophages can be beneficial for angiogenesis, but further mechanistic investigations are required.